Meningkatkan Layanan Pendidikan Dengan Program Bimbingan Belajar Tambahan Bagi Anak-anak Desa Pulantan - Amalia Putri; Hana Aulia; Juli Nur Jannah; Muhammad Husein; Nor Hayati; Nor Maliah; Ita (Kayuh Baimbai : Jurnal Pengabdian Masyarakat, 2024)
Education is something important and must be owned by everyone. Everyone has the right to get a decent education. Students have an important role in society. Through this Real Work Lecture (KKN) program, students can practice and apply their knowledge to village communities, especially in the field or education. This article refers to "Improving Education Services with Additional Tutoring Programs for Children in Pulantan Village". This research aims to accompany and help children who have difficulty learning independently. This research was carried out by KKN students at UIN Antasari Banjarmasin in Pulantan Village, Aluh District, Banjar Regency for 1 month, namely 13 October-13 November 2023. The method used in this research was PAR (Participatory Action Research), which is a method that involves all parties. This type of research is included in the type of qualitative research. The results obtained during this implementation are the enthusiasm and enthusiasm of children in learning, direct assistance and guidance of children, so that learning objectives can be achieved effectively.